Educating Nurses at The College of The Bahamas - Ballance, Virginia C.; McKenzie, Yvonne (International Journal of Bahamian Studies, 2015)
In the first decade following Bahamian Independence in 1973, registered nurse education transformed from a professional training programme offered by the Ministry of Health’s Department of Nursing Education into an academic discipline offered at The College of The Bahamas. The College of The Bahamas began offering an Associate of Arts degree in Nursing in the early 80s, with its first class graduating at the 1986/87 commencement. The diploma and degree programmes operated in tandem, sharing a campus until the Ministry of Health nursing diploma programme was phased out. Its last graduation ceremony was held in 1993. The nursing programme offered by COB evolved from an Associate of Arts to an Associate of Science in Nursing degree and later, in the 2000s, to a Bachelor of Science in Nursing degree. This paper will trace the development of nurse education programmes in the Bahamas from their beginnings to date, highlighting the milestones and achievements.